36.1k views
3 votes
How do I do this? I'm confused.​

How do I do this? I'm confused.​-example-1
User Alf Moh
by
6.0k points

1 Answer

4 votes

Explanation:


\huge\mathcal\blue{here's \: your \: solution} \\ \\ x = 2y - 14 \: \: \: (given) \\ \\ equation \: = 5x - 7y = - 43 \\ \\ now \: put \: the \: value \: of \: x \: in \: equation \\ \\ 5(2y - 14) - 7y = - 43 \\ \\ 10y - 70 - 7y = - 43 \\ \\ 3y - 70 = - 43 \\ \\ 3y = + 70 - 43 \\ \\ 3y = 27 \\ \\ y = 27 / 3 \\ \\ y = 9 \\ \\ now \: put \: the \: value \: of \: y \: in \: equation \\ \\ x = (9 * 2) - 14 \\ \\ x = 18 - 14 \\ \\ x = 4 \\ \\ \huge\mathfrak\red{hope \: it \: helps..}

User Gespinha
by
5.5k points